Investigation of MIG welding to the corrosion behaviour of heat treated carbon steel - Ng, Shing Shian (2012)
The corrosion behaviour of metal inert gas (MIG) welded heat treated carbon steel was investigated. Filler material of ER308L and ER70S were used to complete the butt joint welding on non-heat treated and heat treated low carbon steel (AISI 1010). The welding heat input was manipulated by varying the welding voltage for MIG welding process. The microstructures for welded specimens were analysed with the optical microscope. During the electrochemical test, the corrosion rate on the carbon steel was determined. Microstructural analysis for specimen without cleaning and after cleaning was analysed by using SEM. Results showed that the increase in welding heat input was highly significant to the corrosion rate of carbon steel. The welding heat input was able to change the ferrite content on the microstructure of specimen which affected the corrosion rate on the carbon steel.